2016
DOI: 10.3389/fmicb.2016.00649
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence Analysis of Microbial Taxa in the Atlantic Ocean Reveals High Connectivity in the Free-Living Bacterioplankton

Abstract: We determined the taxonomic composition of the bacterioplankton of the epipelagic zone of the Atlantic Ocean along a latitudinal transect (51°S–47°N) using Illumina sequencing of the V5-V6 region of the 16S rRNA gene and inferred co-occurrence networks. Bacterioplankon community composition was distinct for Longhurstian provinces and water depth. Free-living microbial communities (between 0.22 and 3 μm) were dominated by highly abundant and ubiquitous taxa with streamlined genomes (e.g., SAR11, SAR86, OM1, Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
123
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 119 publications
(193 reference statements)
15
123
1
Order By: Relevance
“…The increased nutrient enrichment occurring in the south could explain the reduced bacterial diversity found in this region (Qurban et al, ). A lower diversity with increasing productivity has been previously observed in other regions and habitats (Milici et al, ; Wemheuer et al, ). Further studies evaluating the importance and role of environmental factors across environmental gradients, as well as investigating seasonal differences, will provide a better understanding of the drivers of microbial reef community assembly and function.…”
Section: Discussionsupporting
confidence: 58%
“…The increased nutrient enrichment occurring in the south could explain the reduced bacterial diversity found in this region (Qurban et al, ). A lower diversity with increasing productivity has been previously observed in other regions and habitats (Milici et al, ; Wemheuer et al, ). Further studies evaluating the importance and role of environmental factors across environmental gradients, as well as investigating seasonal differences, will provide a better understanding of the drivers of microbial reef community assembly and function.…”
Section: Discussionsupporting
confidence: 58%
“…Recent molecular work has shown that particles with diameters > 30 µm (Fuchsman et al ., ), > 20 µm (Salazar et al ., ), > 8.0 µm (Milici et al ., ), > 3.0 µm (Orsi et al ., ; Milici et al ., ) > 1.6 µm (Ganesh et al ., ) and even > 0.8 µm (Salazar et al ., ) are consistently colonized by particular groups of microbes. The PA assemblage in our study (> 2.7 µm) was populated by chemoorganotrophic members of the γ‐proteobacteria, δ‐proteobacteria, Verrucomicrobia, Bacteroidetes and Planctomycetes, all previously shown to be associated with small particles (Fuchsman et al ., ; Ganesh et al ., ; Milici, et al ., ; Salazar et al ., ). Most members of these groups are implicated in both aerobic and anaerobic chemoorganotrophy, suggesting that taxa with varied organic carbon degradation metabolisms can co‐exist in particles.…”
Section: Discussionmentioning
confidence: 99%
“…Many SO 2-4 reducers and fermenters are obligate anaerobes and are likely able to survive in the oxycline and suboxic depths due to sustained anoxia the particles' interior under these conditions. Some taxa in the PA fraction were from the family Bdellovibrionaceae, a predatory clade also found exclusively on particles in other locations (Salazar et al, 2015;Milici et al, 2016). An abundant OTU from Fibrobacteria (group 'P.…”
Section: Microbial Particle Association Through a Redox Gradientmentioning
confidence: 99%
“…The production of siderophores by Marinobacter sp. These findings in combination with the observed co-occurrence of microbial taxa (Gilbert et al, 2012;Lima-Mendez et al, 2015;Milici et al, 2016;Needham and Fuhrman, 2016;Zhou et al, 2018) raise the question of whether interactions have the potential to drive biogeographic patterns of microbial communities in the aquatic environment. Diatom cell division was recently shown to be regulated by the excretion of hormones released by prokaryotes based on the co-cultured Pseudo-nitzschia multiseries with Sulfitobacter sp.…”
Section: Introductionmentioning
confidence: 98%
“…Using the exudate of a common diatom species as a growth substrate in an experimental approach and in situ observations allowed to establish a link between substrate preferences of several prokaryotic taxa and their presence during spring phytoplankton blooms in the Southern Ocean (Landa et al, 2016). The reported co-occurrence patterns between eukaryotic and prokaryotic taxa extend the potential importance of biotic interactions to larger temporal and spatial scales (Gilbert et al, 2012;Lima-Mendez et al, 2015;Milici et al, 2016;Needham and Fuhrman, 2016;Zhou et al, 2018). These networks could in part be driven by the exchange of a suite of metabolites, discovered in experimental studies using model organisms.…”
Section: Introductionmentioning
confidence: 99%